Mnemonic devices techniques to develop and improve vocabulary recall among Grade Vii students - Bermejo, Jayron D. (MSU Gensan Graduate Education Research Journal, 2016)
This study was conducted to determine the effectiveness of Mnemonic Devices in developing and improving vocabulary recall of the Grade VII students of the Notre Dame of Marbel University-Integrated Basic Education Department (NDMU-IBED). The researcher used quasi-experimental method of research. The subjects of the study were 84 Grade VII students who came from Section 2 and Section 3 of the aforesaid school. One section served as control group (use of Traditional Technique) and the other functioned as experimental group (use of Mnemonic Device). Both groups underwent pretest and posttest. T-test for two dependent samples was employed to determine the significant difference between the pretest mean and posttest mean scores of the control group, and pretest and posttest scores of the experimental group, T-test for independent samples was used if there was significant difference between the pretest and the posttest scores of the control and experimental groups. Furthermore, T-test of independent samples was used to determine if there was a significant difference between the mean gain scores of both groups. Based on the gathered data, the following are the findings derived: the students of the experimental and control groups performed FAIR at the start of the study; there is no significant difference in the pretest mean scores of control and experimental groups; there is also a significant difference in the Pretest and Posttest scores of the experimental group and control group; and Mnemonic Devices are effective techniques to improve and develop vocabulary recall.